(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Most of the studies carried out in the field of fertility ignore the lack of knowledge of the fertile period among women of childbearing age, and those that do exist are biomedical in nature, thus leaving the sociodemographic approach on the shelf. In Côte d’Ivoire, 32% of women have a good knowledge of the fertile period against 68% with questionable knowledge. Yet, knowledge of the fertile period is important for birth control and has benefits such as avoiding drug side effects, immediate recovery of fertility and its being free of charge. This study intends to use secondary data from the 2011-2012 EDS-MICS of Côte d’Ivoire to highlight the extent to which the level of unfamiliarity with the fertile period vary among women of childbearing age and investigate related factors. The findings, based on both bivariate descriptive and multiple component factorial analyses, reveal a correlation between lack of knowledge of the fertile period and variables relating to standard of living, place of residence, religion, exposure to the media, marital status, level of education, use of birth control, and the woman’s occupation. Therefore, addressing these variables, would not only help control both fertility, and family planning, but also help achieve the demographic dividend.